KETERAMPILAN PROSES SAINS DAN PEMBELAJARAN IPA DI SEKOLAH DASAR (TELAAH BUKU SISWA KELAS IV SD TEMA 2 KARYA SUMINI) - Anatri Desstya (Profesi Pendidikan Dasar, 2015)
The purpose of this research was to determine aspects of applied learning approach based on scienceprocess skills as a way to transfer material science for students in elementary school. The method usedis the method of library research. The collection and review of reference indicators for science processskills is then connected to the science material in the student book IV theme 2. Researchers analyzed thedata associated with using inductive and deductive. The conclusion that: 1) In each sub-theme has beenreferring to the learning approach science process skills, 2) Each sub-themes are science process skillsare fundamental, namely observation and communication, 3) No founding the activities to formulatehypotheses.